A Digital Technique to Manage Restoration of Severely Tilted Adjacent Implants: A Dental Technique. Issue 5 (27th April 2022) - Hu, Liqun; Sa, Yue
Abstract: Implant placement in close proximity with adverse angulations may result in difficulty with impression making. With the lock surface function provided by intraoral scanning software programs, severely tilted adjacent implants can be digitized one by one without interfering with the accuracy of the digital cast. This article presents a straightforward digital impression technique for severely mesiodistally tilted adjacent implants in a clinical case.